การให้คำปรึกษาทางพระพุทธศาสนากับตะวันตกเพื่อคลายทุกข์ในสังคมไทย - สุวรรณ, กาญจนพงศ์ (วารสารศรีล้านช้างปริทรรศน์, 2017)
กระบวนแก้ปัญหาเพื่อให้คลายจากความทุกข์ต่าง ๆ ที่พระพุทธเจ้าได้ค้นพบ พร้อมทั้งสั่งสอนเหล่าพุทธบริษัทให้ประพฤติปฏิบัติตามคําสั่งสอนของพระพุทธองค์ คือ ช่วยเหลือมนุษย์ให้สามารถช่วยตนเอง และเป็นที่พึ่งของตนเองได้ ตลอดถึงการเป็นที่พึ่งโดยเฉพาะด้านจิตใจกล้าเผชิญความจริง เข้าใจเรื่องอารมณ์ของตนและคนอื่น ดูลมหายใจเข้า-ออกพร้อมปรับฝึกภาวะที่จะรับสิ่งใหม่ ๆ ที่เกิดขึ้น ทำให้ผู้รับบริการเกิดมีความคิดในแง่บวก มีจิตเมตตาต่อเพื่อนมนุษย์ได้พร้อมพิจารณาถึงไตรลักษณ์ และอยู่ในอารมณ์ปัจจุบัน มีวิธีคิดที่แยกแยะอย่างแยบคลายมาเป็นแบบแผนในการปฏิบัติเพื่อฝึกหัดฝึกฝนทางด้านจิตเป็นสำคัญ ส่วนตะวันตกให้คำปรึกษาคลายทุกข์ว่าความทุกข์ของบุคคลเกิดในระดับความรู้สึกขัดแย้งในตนเองไม่มีจุดมุ่งหมายในชีวิตไม่มีอิสระภาพเกิดเบื่อหน่ายในชีวิตที่บีบคั้นเข้ามาการให้คำปรึกษาก็คือให้กำลังใจตระหนักรู้ในตนเองยอมรับบอกจุดหมายในชีวิตทั้งระยะสั้นและระยะยาวพร้อมกับพัฒนาเพื่อไปสู่จุดหมายนั้นอีกทั้งกล้ารับผิดชอบการกระทำของตนสามารถกำหนดแก้ปัญหาด้วยตนเองมีเสรีภาพค้นพบและยอมรับทุกข์พร้อมทั้งหาทางระบายทุกข์และรับผิดชอบในประสบการณ์ของตนเองทั้งทางด้านความคิดความรู้สึกและการกระทำรู้จักพึ่งพาตนเองรู้จักเป็นผู้รับและผู้ให้ที่เหมาะสม The solution to the problem of relief from suffering. The Buddha discovered. The Buddha taught the company to follow the teachings of the Buddha is to help human beings to help themselves. And it is their own. It is a good place to be. Dare to face the truth understand their emotions and others. See the breath-out and adjust the training to receive new things happen, resulting in positive thinking in the service. Have mercy on human beings, and consider the Trinity. And in the present mood. There are ways to think badly. It is a practice in practice. Mental training is important. Western counselors relieve the suffering of the person born in the sense of self-contradictions. No purpose in life No freedom I'm tired of life in the squeeze. The counseling is to encourage self-awareness, to acknowledge the short-term and long-term goals of life, and to develop to that end. They are responsible for their actions. Can determine self-solution, freedom, discovery and acceptance of suffering. And find the way out. And responsible for their own experiences. Both thoughts, feelings and actions are self-reliant. Recognize the right recipient and provider.